2021
DOI: 10.21203/rs.3.rs-868127/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Borderline Personality Disorder in Young People: Associations with Support and Negative Interactions in Relationships with Mothers and a Best Friend

Abstract: Background:Impaired interpersonal functioning has been highlighted as a core feature of borderline personality disorder (BPD). Adolescence and young adulthood form important developmental stages within both the emergence of BPD and the development of interpersonal functioning, which takes place mostly in relationships with parents and friends. This study aimed to: (i) investigate relations between BPD symptoms and both supportive and negative interactions with mothers and best friends; (ii) investigate whether… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Next, as expected, we found that negative interactions with parents were related to the more severe level of personality functioning, independently from adolescents' age. This is comparable to previous research showing an association between negative experiences in relationships with parents such as parental control or coercive parenting and aspects of personality pathology [14,26,30]. Thus, discordant qualities of relationship with parents stand out as a potentially important factor for the prediction of higher levels of impairment in personality functioning.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Next, as expected, we found that negative interactions with parents were related to the more severe level of personality functioning, independently from adolescents' age. This is comparable to previous research showing an association between negative experiences in relationships with parents such as parental control or coercive parenting and aspects of personality pathology [14,26,30]. Thus, discordant qualities of relationship with parents stand out as a potentially important factor for the prediction of higher levels of impairment in personality functioning.…”
Section: Discussionsupporting
confidence: 84%
“…Authors explain that adolescents at risk for a personality disorder might experience the interactions with a best friend at a more extreme level with friendships providing a ground for both supportive and negative interactions. Since personality disorders are marked by serious disturbances in interpersonal functioning, this was considered as a marker of BPD in the studied sample [30]. However, we investigated a community-based sample so we hypothesize that intense involvement in peer relationships might also be the marker of the normative shift from parent to peer influence that is common for this developmental stage [20,58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations